Atenção em HIV/AIDS na Atenção Básica: um estudo da rede de Rio Claro - Peixoto, Cacilda (Universidade Federal de São Carlos, 2020)
Acquired Immunodeficiency Syndrome (AIDS) corresponds to the clinical manifestation of infection by the Human Immunodeficiency Virus (HIV). Despite advances in the fight against the HIV / AIDS epidemic, it remains a public health problem, with significant data on morbidity and mortality and obstacles that need to be overcome. In view of the global scenario that points to high levels of HIV contamination and the need to offer actions aimed at reducing the spread of the disease, starting in 2003, the process of decentralizing HIV testing and counseling in primary care has intensified, allowing greater coverage and accessibility, and so far this action has been centralized in specialized care services. In this context, the study aimed to evaluate HIV / AIDS care in primary care, under the evaluative opinion of professional nurses. This is a research with a quantitative approach. The participants were 22 nurses who work in the Basic Health Units and Family Health Strategy in the city of Rio Claro / SP. Data were collected through a questionnaire from October 2019 to January 2020 and analyzed by calculating the Average Ranking (RM), Cronbach's alpha coefficient and descriptive statistics through the SPSS (Statistical Package for the Social Sciences) programs and STATA (Statistical Software). The results showed a weakness in the performance of the units in relation to the domains: Health Education, Permanent Education in Health and Prevention of Sexually Transmitted Infections. It was observed that the units perform a very satisfactory work in relation to actions such as: the provision of rapid testing, provision of protective supplies (condoms), prevention of vertical HIV transmission and early diagnosis, thus valuing the ability of AB in actions that can weaken the spread of the virus infection. It is signaled that the best performances were expressed in those more standardized actions, with a tendency to standardization and of a more technical character, when compared to actions of a more procedural, communicational nature and that require singularization of approaches focusing on specificities and needs. Thus, it is necessary to advance in comprehensive care and, in particular, in prevention that integrates the technical protocol domains with the psychosocial and educational domains in health, with regard, above all, to the approach to the experiences of sexuality, diverse and plural, to the mitigation of stigma of AIDS and social and health inequities. We emphasize, therefore, that the implementation of new structural, technological and procedural arrangements, as well as the interactions between managers, health professionals and users, should focus on overcoming difficulties and implementing humanized and resolutive practices in the control of the HIV epidemic / AIDS at this level of care.
Attention to HIV/AIDS in Primary Care: A study by the RioClaro network
Keywords: HIV; Atenção Básica; Descentralização; Enfermagem; HIV; Primary care; Descentralization; Nursing; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA